Current Solutions for the Treatment of Patients with Urogenital Candidosis and Evaluation of Clinical and Mycologic Efficacy - F.N. Nuraliev (Zien Journals, 2023)
Objective of the study to determine clinical and mycological efficacy of urogenital candidiasis treatment in dynamics depending on sex and place of residence of patients
Keywords: Urogenital candidiasis; vaginal candidiasis; treatment; clinical and mycological efficacy